PENGARUH CUSTOMER RELATIONSHIP MARKETING, DAN NILAI PELANGGAN TERHADAP LOYALITAS KONSUMEN - Saputra, Dendi; Zamhari; Ruben Manullang, Rizal (STIE IBEK Pangkalpinang, 2022)
The theories used in this research are management theory, marketing theory, customer relationship marketing theory, customer value theory, and consumer loyalty theory. The method used in this research is to use a quantitative approach through a census sample approach, which is a sampling technique that provides equal opportunities for each element (member) of the population to be selected as a member of the sample. According to Sugiyono (2008), “saturated sampling or census is a sampling technique when all members of the population are used as samples. Another term for saturated sampling is census.” The sampling method used in this study is the saturated sample method. The number of sampling in this study was 30 shops that became the target of this study. The results of this study show the results of Adjusted R2 value of 0.625 or can be defined as equivalent to 62.5%. It can be concluded that customer relationship marketing and customer value can explain the positive influence on consumer loyalty of 62.5%. The remaining 37.5% can be explained by other variables not used in this study. There is a significant influence of customer relationship marketing variables on consumer loyalty. This means that the t-test produced by individual customer relationship marketing research has a significant and positive influence on consumer loyalty. H1 is accepted with a value of 3.572 and a P-Value of 0.001. There is a significant effect of the customer value variable on consumer loyalty. This means that the t-test produced by individual research has a significant and positive influence on customer loyalty. H2 is accepted with a value of 3.353 and a P-Value of 0.002. The fourth hypothesis from the F test is that the values ​​obtained by consumer satisfaction, marketing communication, and customer values ​​have a positive and significant effect on consumer loyalty at PT ASW Area Pangkalpinang City, Tamansari District, H1 is accepted, H3 is accepted, and the result is a value of 24,537 and P-Value <.001.